Investigate the influence of nothes on stresses for mild steel and aluminum - Norul Hisyam, Md Sabri (2009)
The diameter and type of notches has the influence to stresses any of design that has the notches. So, there is lot of research been done about the relationship of notches and stress. Many failures in engineering applications or machine components have been caused by notches at which stress was concentrated. Hence, the main objective of this study is to investigate the influence of notches on stresses for mild steel and aluminum. The investigation was based on the types and radius of notches. Both experiment and simulation were done in order to validate the result. The experiment was carried out by using tensile test to obtain maximum stress to the specimen while the simulation was analyzed by using ALGOR V22 software to obtain the stress of the specimen. The material that used in the experiment is mild steel and aluminum and for ALGOR V22 is steel ASTM-A36 and aluminum alloy 1100-H14. The experimental results and the finite element analysis results show that the maximum stress will decrease when the ratio r/d is increase. Thus, the influence of notches on the stresses has been evaluated.